Navigating Common Good for Religious Moderation in Indonesia's Multicultural - Nia Nur Pratiwi; Putu Ayu Suniadewi (Pancasila: Jurnal Keindonesiaan, 2024)
As a nation with highly multicultural societies, Indonesia comprises various ethnic groups, customs, cultures, and religions. This often triggers societal conflicts between tribes, cultures, and beliefs. For this reason, a model or approach is needed to increase tolerance and respect. Therefore, the researchers carry the concept of the Common Good as a concept of universal religious moderation through a philosophical approach that integrates the idea of the common good in the context of universal religious moderation. This concept emphasizes the need for cooperation between various beliefs to achieve common goals in creating an inclusive and harmonious society by emphasizing universal moral principles in developing a framework for religious moderation. Specifically, this research aims to apply the concept of the common good as a universal religious moderation value in Indonesian society as a nation with a significant plurality. The method used in this research is qualitative library research using secondary data. The results formulate the concept of universal religious moderation by carrying the idea of the common good as a solution to the problems of diversity and plurality of religions, cultures, tribes, ethnicities, and groups in Indonesia as a nation with a high level of multicultural communities.